Effects of metaphyseal bone tumor removal with preservation of the epiphysis and knee arthroplasty - ZHANG, PENG (D.A. Spandidos, 2014)
In this study, the effects of surgical removal of malignant metaphyseal bone tumors with epiphysis preservation and knee arthroplasty were analyzed. A total of 15 patients with malignant metaphyseal bone tumors were investigated. Six of these patients underwent epiphyseal preservation surgery with preoperative physeal distraction, termed the physeal distraction (PD) group. Nine patients underwent resection of the knee joint, combined with metal prosthesis transfer, termed the knee arthroplasty (KA) group. Tumor control, limb length discrepancy, range of movement (ROM) of the knee and functional outcome of lower limb [Musculoskeletal Tumor Society (MSTS) score and the Toronto extremity salvage score (TESS)] were assessed for these two groups. All 15 patients were followed-up after the surgery. One patient in the PD group was found to have lung tumor metastasis; however, no local tumor recurrence was found. In the KA group, local tumor recurrence was found in one patient, and lung metastases were observed in two cases postoperatively. The limb length discrepancy in patients of the PD group was 2.58±0.27 cm, which was significantly less compared with that in patients in the KA group (4.01±0.13 cm; P<0.05). In addition, the lower limb knee ROM in patients in the PD group was 127.70±14.63°, which was increased compared to that in patients in the KA group (105.70±15.48°; P<0.05). The mean MSTS score was 86.67% with a mean TESS of 82.33% in patients from the PD group, which showed no significant difference compared with the respective scores for patients in the KA group (P>0.05). Therefore, epiphyseal sparing limb-saving surgeries should be considered for the treatment of malignant metaphyseal bone tumors in children, when certain indications are satisfied.